Penggunaan Aplikasi Google Meet dalam Meningkatkan kepercayaan Diri Mahasiswa - Nurman Hakim Armaindo; Choirul Ulil Albab (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of using the Google Meet application and the ease of online discussion on students' self-confidence levels at the Faculty of Computer Science of Dian Nuswantoro University. University learning has turned using online communication media like the Google Meet application since the government issued a circular letter during the Covid-19 pandemic. However, the transition may affect students' psychology, particularly their self-confidence. This study applied behaviorist communication theory, new media theory, and technological determination theory. This study used a quantitative approach with an explanatory approach. Primary and secondary data was obtained from questionnaires distributed to 98 respondents and from a literature study. The results showed that the variable of using the Google Meet application had a 33.4% and the ease of online discussion variable had a 60.5% effect on students' self-confidence levels. The F test's results showed that the use of the Google Meet application and the ease of online discussion on students' self-confidence levels had an F count of 28.133 > F table of 2.36, indicating a positive and significant effect. The R-Squared value was 37.2%, with the remaining 62.8% coming from the influence of variables beyond this study.